France. - Grolier Educational (Firm) (Danbury, CT : Grolier Educational, 1999)
Describes the customs and beliefs connected to some of the special occasions celebrated in France, including Carnaval, Bastille Day, and Christmas. Includes recipes and related activities.
Includes index.
Keywords: Festivals -- France -- Juvenile literature; Festivals -- France; Holidays -- France; Fiesta; France -- Social life and customs -- Juvenile literature; France -- Social life and customs